Musicians performing at a Government Camp - Thomas Hart Benton (artist):::Creator::::::::::::
Three musicians performing at a Government Camp; from The Grapes of Wrath. Fiddler player is standing with guitar and banjo players sitting. "The fiddle squeaks and the guitar bongs. Mouth-organ man is red in the face." "Play more--play the story songs--'As I walked out on the streets of Laredo."'